The Arab masses in Israel - Ghnadreh, Sameeh (Faith and the Intifada, 1992)
Information is given on the Arab national minority inside Israel, whose special status derives from the fact that they are part of the Arab Palestinian people yet they have the Israeli identity as citizens of the state of Israel. The author examines features of discrimination concerning this group. (DÜI-Mjr)